The Crime of Kidnapping with Aggravation According to Islamic Criminal Law - Afrianti, Tika; Lubis, Syaddan Dintara (SIGn Jurnal Hukum, 2025)
The fragmentation of regulations on the crime of kidnapping within the Indonesian legal system—scattered across the Penal Code and sectoral laws—creates normative inconsistencies that risk injuring legal certainty. This condition necessitates a more coherent penal framework that is substantively just. On the other hand, Islamic criminal law (fiqh jinayah) categorizes kidnapping (ikhtithaf) as a ta’zir offense, which offers a flexible sanctioning mechanism based on the principles of maqashid syariah. This research offers a comparative analysis to bridge these normative inconsistencies by introducing the sanction aggravation framework of fiqh jinayah as a critical evaluative lens. Using a normative juridical method with statutory, conceptual, and comparative law approaches, this study analyzes primary and secondary legal materials from both legal traditions. The findings reveal a fundamental philosophical difference: positive law applies a rigid, procedurally-oriented system of sanction gradation, whereas fiqh jinayah provides a holistic and adaptive framework for punishment aggravation based on substantive justice. This penal model in fiqh jinayah is dynamically determined by the degree of violation against the protection of life (hifz al-nafs), lineage (hifz al-nasl), and property (hifz al-mal), while comprehensively considering victim characteristics, the modus operandi, and the consequences inflicted.